Photocatalytic and biocidal activities of novel coating systems of mesoporous and dense TiO2-anatase containing silver nanoparticles - Roldan, Maria Virginia (2014)
Here we describe the development of novel nanostructured coating systems with improved photocatalytic and antibacterial activities. These systems comprise a layer of SiO2 followed by a layer of mesoporous or dense TiO2-anatase, and doping with silver nanoparticles (Ag NPs). The coatings were synthesized via a sol–gel technique by combining colloidal Ag NPs with TiO2 and SiO2 sols. The photocatalytic activity was studied through methyl orange decomposition under UV light. Results showed a great increase of photocatalytic activity by Ag NPs doping. The most active photocatalyst corresponded to the Ag–SiO2/TiO2 mesoporous system, associated with the porosity of the coatings and with the decrease of e–h recombination for the presence of Ag NPs. All the TiO2 coatings showed a strong bactericidal activity against planktonic forms of Gram-negative (enterohemorrhagic Escherichia coli) and Gram-positive (Listeria monocytogenes) pathogens, as well as a strong germicidal effect against deadly spores of human gas gangrene- and anthrax-producing bacteria (Clostridium perfringens and Bacillus anthracis, respectively). The bactericidal and sporocidal activity was improved by doping the coatings with Ag NPs, even more when nanoparticles were in the outer layer of TiO2, because they are more accessible to the environment. The mechanisms responsible for the increase of photocatalytic and bactericidal behaviors related to Ag NP doping were studied by spectroscopic ellipsometry, UV–vis spectroscopy, photoluminescence and anodic stripping voltammetry. It was found that the separation of the electron–hole pair contributed to the enhancement of photocatalysis, whereas the effect of the local electric field reinforcement was probably present. A possible involvement of a decrease of band-gap energy and dispersion by silver nanoparticles is ruled out. bactericidal efficacy was increased by Ag+ ion release. Overall, the results included in this article show that the architecture of the films may tune photocatalytic and bactericidal properties.